Active, Creative, Effective, and Enjoyable Learning (PAKEM) with the Utilization of Smart TV to Realize Interactive Islamic Education Learning - Muthia Arin Shafa; Muhammad Muzzammil Akbar; Muhammad Adil Amrullah; Zaini Tamim AR (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2026)
Purpose of the study: This study aims to analyze the implementation of the Active, Creative, Effective, and Enjoyable Learning (PAKEM) approach integrated with Smart TV technology to create an interactive, collaborative, and student-centered Islamic Religious Education (PAI) learning environment. Methodology: This study employed a qualitative descriptive research design using a literature review approach. Data were collected from reputable scientific journal articles indexed in SINTA and published between 2016–2026. The study utilized content analysis, thematic data reduction, theoretical categorization based on the TPACK framework, source triangulation, and theoretical synthesis techniques. Main Findings: The findings indicate that Smart TV functions as a multisensory instructional center that transforms abstract Islamic concepts into dynamic visual and audio learning experiences. The PAKEM approach promotes active participation, collaboration, critical thinking, and student engagement. The integration of Smart TV and PAKEM creates an interactive digital learning ecosystem, enhances motivation, supports real-time feedback, and strengthens meaningful spiritual reflection in Islamic Religious Education. Novelty/Originality of this study: The novelty of this study lies in the theoretical integration of the TPACK framework with the PAKEM approach and Smart TV technology specifically for Islamic Religious Education. It introduces a digital interactive classroom ecosystem that combines pedagogical strategies and interactive screen technology, providing a new model for enhancing student engagement, collaboration, and meaningful religious learning experiences.